Lexical access in children with hearing loss or specific language impairment, using the cross-modal picture–word interference paradigm. (February 2015) - de Hoog, Brigitte E.; Langereis, Margreet C.; van Weerdenburg, Marjolijn; Knoors, Harry; Verhoeven, Ludo
Highlights: Language processing difficulties affects lexical access in picture naming. Children with SLI have poorly specified representations of words. Children with hearing loss can construct solid representations of words. Lexical access improvement deserves specific attention in SLI therapy and education. Abstract: In this study we compared lexical access to spoken words in 25 deaf children with cochlear implants (CIs), 13 hard-of-hearing (HoH) children and 20 children with specific language impairment (SLI). Twenty-one age-matched typically developing children served as controls. The children with CIs and the HoH children in the present study had good speech perception abilities. We used a cross-modal picture–word interference paradigm to examine lexical access. Results showed that children with SLI revealed overall slower reaction times and produced more errors than the children with CIs, the HoH children, and the control children. Reaction times of children with CIs and the HoH children did not differ from those of the control children. Thus, problems with spoken language processing, as is the case in children with SLI, seem to affect lexical access more than limitations in auditory perception, as is the fundamental problem in children with hearing loss. We recommend that improvement of lexical access in children with SLI deserves specific attention in therapy and education.